Magnetoacoustic wave propagation in the solar corona and filament dynamics - Sabri Somaiyeh; Poedts Stefaan (Scientific Reports)
Abstract The formation of a S-shaped filament was investigated to determine if and how magnetoacoustic waves in the solar corona can trigger filament excitation. The study investigated how magnetoacoustic waves interact with two magnetic null points in the solar corona. Since the solar corona has a complex magnetic field structure, it is expected that magnetic structures are predominantly responsible for the occurrence of coronal events. Simulation methods are required because of the complex nature of the reconnection problem and the way MHD waves behave. Because of notable progress in the production of supercomputers and the enhancement of techniques, it is now possible to analyze the behaviour of nonlinear plasma near the magnetic null point through numerical methods. This article aims to explore the idea of a 2.5D null point pair and investigate the motion and generation of plasma flow resulting from a solitary magnetoacoustic pulse passing through a particular magnetic structure that contains two null points. In this statement, the PLUTO code, which is a type of code called Godunov, is used to solve a set of equations known as resistive magnetohydrodynamic equations. It was depicted that when transitioning from X-point to O-point, twisted formations are formed, which play a significant role in developing S-shaped filaments. These formations also have a vital function right before the excitement of the filaments.